Combining ability and heterosis studyin maize inbreds throughout diallel mating design (Bangladesh Journal of Agricultural Research, 2018)
Combining ability effects were estimated for grain yield and some other important agronomic traits of maize in a 7×7 diallel analysis excluding reciprocals. The variances for general combining ability (GCA) were found significant for yield, days to pollen shedding, days to silking and ear height while it was found non-significant for plant height and number of kernels/ear. Non-significant general combining ability (GCA) variance for plant height and number of kernels/ear indicates that these two traits were predominantly controlled by non- additive type of gene action. Specific combining ability (SCA) was significant for all the characters except yield and days to silking. Non-significant specific combining ability (SCA) variance for yield and days to silking suggests that these two traits were predominantly controlled by additive type of gene action. Both GCA and SCA variances were found significant only in days to pollen shedding and ear height indicated the presence of additive as well as non additive gene effects for controlling the traits. However, relative magnitude of these variances indicated that additive gene effects were more prominent for all the characters studied except days to silking. Parent BIL95 was the best general combiner for both high yield and number of kernels/ear and parent BML4 for dwarf plant type. Two crosses (BML4× BML36 and BIL114× BIL31) exhibited significant and positive SCA effects for grain yield involved low × average and average × average general combining parents. The range of heterosis expressed by different crosses for grain yield and days to silking was from -65.83 to 21.26 percent and -17.85 to 8.22 percent, respectively.. The better performing three crosses (BIL114×BIL31, BIL138×BIL95 and BIL31×BIL95) can be utilized for developing high yielding hybrid varieties as well as for exploiting hybrid vigour.Bangladesh J. Agril. Res. 43(4): 599-609, December 2018